Pragmatyczne i dydaktyczne uwarunkowania rozumienia tekstu obcojęzycznego - Woźniewicz, Władysław (Studia Rossica Posnaniensia, 2016)
The article describes the linguistic, cultural, pragmatic conditions necessary for understanding  foreign language texts. The main postulate of the article is that  an adequate understanding of a text is dependent both on knowing the meaning of the individual words and interpreting their meaning in the text as a whole. A substantial and crucial part of the article is dedicated to the description of didactic activities  for teachers aiming to develop the skills required for understanding foreign texts, both for beginners and advanced learners.